2015
DOI: 10.1063/1.4915948
|View full text |Cite
|
Sign up to set email alerts
|

On the interplay between phonon-boundary scattering and phonon-point-defect scattering in SiGe thin films

Abstract: This paper provides theoretical understanding of the interplay between the scattering of phonons by the boundaries and point-defects in SiGe thin films. It also provides a tool for the design of SiGe-based high-efficiency thermoelectric devices. The contributions of the alloy composition, grain size, and film thickness to the phonon scattering rate are described by a model for the thermal conductivity based on the single-mode relaxation time approximation. The exact Boltzmann equation including spatial depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Significant progress took place when Garg et al demonstrated the viability of first principle approaches to estimate the bulk thermal conductivity of SiGe [6]. Recently, Iskandar modeled thin SiGe films to include the effect of boundary modes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress took place when Garg et al demonstrated the viability of first principle approaches to estimate the bulk thermal conductivity of SiGe [6]. Recently, Iskandar modeled thin SiGe films to include the effect of boundary modes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusive transport assumption remains valid if the heat source dimension a is bigger than the carrier mean free path (MFP), l. That is if the system Knudsen number (Kn = l/a) is smaller than 1 (Kn << 1). In our system, phonon MFP is greatly reduced compared to bulk values due to interface scattering and impurities [164].…”
Section: Thermal Transport In Anisotropic Mediamentioning
confidence: 89%
“…It is also possible that the Ge content does not increase linearly inside the layer and that some Ge accumulated at the top. Finally, we model thermal conductivity using bulk thermal conductivity values whereas this value can be greatly reduced in thin film [164,175].…”
Section: Thermal Transport In Anisotropic Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the increased scattering events of heat carriers significantly reduce the thermal conductivity and give rise to important thermal issues, primarily stability. 14,15 The ability to effectively dissipate heat is therefore a crucial limiting factor in integrated photonic circuit design, due to the fact that device functionality and performance strongly depend on the temperature. In particular, for semiconductor coherent light sources, the yield usually decreases above room temperature while the threshold current increases rapidly with temperature.…”
Section: Introductionmentioning
confidence: 99%